Islamic Character Education in E-Learning Model: How Should It be Implemented? - Mustofa, Mutmainnah; Ahmadi, Rulam; Karimullah, Imam Wahyudi (Jurnal Sains Sosio Humaniora, 2020)
Recently, studies examining the inclusion of Islamic character education in schooling sectors have been exclusively discerned. The research mainly focused on teachers’ and students’ perceptions, curriculum and materials development, as well as policy implementation. Albeit the results of these studies shared significant insights in teacher education programs, very sparse discussions were carried out with regard to how the Islamic character education should be enacted. Interestingly, virtual education nowadays also challenges the implementation of this notion. In this work, therefore, we propose a model of Islamic character education cultivation employing e-learning approach in a schooling context. The use of participatory action research (PAR), additionally, is encouraged to capture learning cycles of Islamic character in the classroom between teachers and students. This proposal, if implemented by teachers, would contribute to better realization of moderate teachings of Islam through character education.